Reconstruction of Pelvic Ring after Hemipelvectomy and Fibular graft at 39 – years – old man with Aneurysmal Bone Cyst at Iliac bone: A Case report - Budi M.N.S.; Ismono D; Hendy Rachmat Primana Lubis; Tua, S.J.R. (Sriwijaya Journal of Surgery, 2020)
Introduction: The ABC (Aneurysmal Bone Cysts) lesion has been reported in the orthopedic literature for more than 60 years; it was first described in 1942 by Jaffe and Lichtenstein. Aneurysmal bone cyst (ABC) in pelvic is a benign, expansile osteolytic lesion that typically affects the metaphysis of long bones in the second decade of life and occurring in patients less than 20 years. The Several ABC treatment modalities had been utilized including wide resection, intralesional resection/curettage with or without different adjuvants, radiation, embolization, intralesional sclerotherapy. Case Report: We present a rare case of a huge aneurysmal bone cyst (ABC) in the iliac bone, occurring in the male patient 4th decade of life. The patient presented with a history of pain and huge pelvic mass size 8x6x5 cm extend to abdominal region for 5 years. Plain radiograph and computed tomography showed expansile lytic lesion arising from the all right iliac bone extend to Lumbar 5. A biopsy was performed and histology confirmed diagnosis of aneurysmal bone cyst. The patient was managed surgically with hemipelvectomy type 1 and Autogenous bone graft from fibula and reconstruction with plate and screw for pelvic ring with and re- attach the muscle on it. Follow up 5 months after surgery the patient can squat and stand maximally with no pain, nor recurrence and can return to normal activity. Conclusion: Early diagnosis and complete resection of tumor and treatment of relevant symptoms represent a viable treatment for this rare disorder to achieve increased life expectancy, low recurrence of tumor and improved quality of life.